Rehabilitation After Gluteus Medius and Minimus Treatment - Victor M. Ilizaliturri, Jr., M.D; Rafael Zepeda Mora, M.D; Liliana Patricia Rodríguez Vega, M.D (Elsevier, 2022)
We reviewed the current literature regarding rehabilitation after gluteus medius and minimus tears as part of a conservative management or postoperative protocol. The greater trochanteric pain syndrome includes a constellation of pathologies that generate pain in the greater trochanteric region and may be accompanied by varying degrees of hip abductor disfunction. It may be related to tendinitis of the gluteus medius and minimus, greater trochanteric bursitis, or even formal tears of the hip abductor tendons. The initial management strategy of the hip abductor tears is conservative, including different anti-inflammatory therapies such as physical therapy and cortisone and platelet-rich plasma injections. The clearest indication for surgical management is failure of conservative management and loss of abductor muscle power. Surgical management has been performed both open and endoscopic with good reported clinical results. More severe tears typically require a more rigid and complex type of fixation. Exorcise intervention seem to improve symptoms after 4 months to a year of therapy therefore a very close supervision of the rehabilitation protocol is mandatory. Gluteus medius and minimus tears are frequent and may be not diagnosed timely. Treatment of these of lesions is based on the knowledge of pathomechanics involved and the extent of injury to the tendon and muscle tissue. Conservative management is based on protecting the hip abductor tendons from excessive tensile and compression stresses while applying progressive load in conjunction with physical and medical anti-inflammatory measures. Surgical treatment is indicated when conservative management fails or an abductor power deficit is associated with pain. Similar physical therapy protocols to those used in conservative management are used postoperatively. Level of Evidence: Level V, expert opinion.